2012
DOI: 10.1159/000332347
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of Angiotensin II Receptors in the Portosystemic Collaterals of Portal Hypertensive and Cirrhotic Rats

Abstract: Background/Aims:In liver cirrhosis/portal hypertension, collaterals as varices may bleed and are influenced by vasoresponsiveness. An angiotensin blockade ameliorates portal hypertension but the influence on collaterals is unknown. Methods:Portal hypertension and cirrhosis were induced by portal vein (PVL) and common bile duct ligation (BDL). Hemodynamics, real-time PCR of angiotensin II receptors (AT1R, AT2R) in the left adrenal vein (LAV, sham) and splenorenal shunt derived from LAV (PV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 73 publications
0
4
0
Order By: Relevance
“…BDL is a well-established technique to induce secondary biliary cirrhosis with NO over-expression and hepatopulmonary syndrome [36]. It has been applied in our previous studies addressing the vasoresponsiveness in cirrhosis [37], [38]. Hepatotoxins, such as carbon tetrachloride (CCl 4 ), have also been used to elicit cirrhosis.…”
Section: Discussionmentioning
confidence: 99%
“…BDL is a well-established technique to induce secondary biliary cirrhosis with NO over-expression and hepatopulmonary syndrome [36]. It has been applied in our previous studies addressing the vasoresponsiveness in cirrhosis [37], [38]. Hepatotoxins, such as carbon tetrachloride (CCl 4 ), have also been used to elicit cirrhosis.…”
Section: Discussionmentioning
confidence: 99%
“…The main reason could be that some spontaneous shunts were retained intra-operatively, thus further reducing the portal blood flow and hepatic sinusoidal pressure and increasing the hepatic artery flow velocity [23,24]. Moreover, the vasodilator mediators, including nitric oxide, were inactivated in liver due to shunts [25,26]. In our study, HAF and SMVF increased significantly after SD-PDPV procedure, due to the decreasing of PVF to liver.…”
Section: Uni-and Multivariate Analysis Of Predictors For Postoperativmentioning
confidence: 50%
“…Role of RAAS on portal pressure provides a new therapeutic alternative [35]. Animal model studies and clinical trials have shown that blockade of Ang II type 1 receptor (AT1R) significantly reduced portal perfusion pressure and HVPG [36][37][38][39]. ACE inhibitor also effects to reduce portal pressure in cirrhotic patients [40].…”
Section: Raasmentioning
confidence: 99%